2022
DOI: 10.1177/87551225211073942
|View full text |Cite
|
Sign up to set email alerts
|

Potential Drug Interactions Between Psychotropics and Intravenous Chemotherapeutics Used by Patients With Cancer

Abstract: Introduction: Patients undergoing cancer treatment usually have comorbidities, and psychiatric disorders are commonly seen in these patients. For the treatment of these psychiatric disorders, the use of psychotropic drugs is common, turning these patients susceptible to untoward drug interactions. Therefore, the aim of this study was to estimate the prevalence of clinically relevant drug–drug interactions (DDI) between chemotherapeutic and psychotropic agents in patients with cancer treated at an oncology serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Anticholinergic side effects of amitriptyline, especially constipation, should be kept in mind in patients taking opioids. Moreover, as other TCAs, amitriptyline could inhibit CYP2C19 threatening the efficacy of cyclophosphamide [32], and its administration with Oxaliplatin could lead to an increased risk of QT interval prolongation [49]. Moreover, hormone replacement therapy (oestrogens), cimetidine (inhibiting CYP1A), fluvoxamine, fluoxetine, paroxetine, bupropion, and duloxetine (inhibiting CYP2D6) could increase its blood levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anticholinergic side effects of amitriptyline, especially constipation, should be kept in mind in patients taking opioids. Moreover, as other TCAs, amitriptyline could inhibit CYP2C19 threatening the efficacy of cyclophosphamide [32], and its administration with Oxaliplatin could lead to an increased risk of QT interval prolongation [49]. Moreover, hormone replacement therapy (oestrogens), cimetidine (inhibiting CYP1A), fluvoxamine, fluoxetine, paroxetine, bupropion, and duloxetine (inhibiting CYP2D6) could increase its blood levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the metabolic effects of these compounds, other side effects such as extrapyramidal symptoms, orthostatic hypotension, QTc interval prolongation, arrhythmias, and haematological consequences should be considered. In particular, quetiapine with oxaliplatin could determine an increased risk of QT interval prolongation [49]. Furthermore, and particularly important in breast cancer patients, antipsychotics could also lead to hyperprolactinemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this study is the first to evaluate the prevalence of docetaxel drug-drug interactions using a nationwide database. Although direct comparisons are not possible due to the use of different study designs, anticancer agents, and databases, the two reported overall prevalences of DDIs for anticancer medications were 32.4% or 26.4%, and when limited to significant drug-drug interactions, the prevalences for anticancer medications were 28.4% or 9.7% [22,23].…”
Section: Discussionmentioning
confidence: 99%